Advances in the management of unresectable or metastatic pancreatic neuroendocrine tumors: Chemotherapy, targeted therapy, hormonal treatment, and future directions - Bilici, Ahmet (Asian Pacific Organization for Cancer Prevention, 2015)
Pancreatic neuroendocrine tumors (pNETs) are rare and heterogenous tumors and surgery to remove the primary tumor is the mainstay of treatment for resectable disease. However, curative surgery is often not feasible, because half of patients with pNET have metastases at the time of diagnosis. Palliative dubulking surgery and liver-directed therapies are appropriate options for these patients. Streptozocin-based regimens are standard, although temozolamide-based treatments are rapidly gaining wide clinical application. Somatostatin analogs are mainly indicated in hormonally active tumors to ameliorate symptoms. In addition, anti-tumoral activity has been proven in well-differentiated NETs. Recently, there has been tremendous progress in the molecular biology of pNETs; thereby, the efficacy of sunitinib and everolimus in the treatment of patients with metastatic pNETs has been proven by large placebo-controlled phase III trials. Currently, there are no definitively proven predictive biomarkers to evaluate response to medical therapies in patients with pNET. Therefore, further studies are needed to individualize and optimize their management. This article reviews systemic chemotherapy, targeted therapies, and anti-secretory treatments for the management of patients with unresectable or metastatic pNETs, summarized in the light of recent advances.
Keywords: Chemotherapy; Neuroendocrine Tumors; Pancreatic; Somatostatin Analogues; Targeted Therapy